2012
DOI: 10.1093/nar/gks906
|View full text |Cite|
|
Sign up to set email alerts
|

CAF-1-induced oligomerization of histones H3/H4 and mutually exclusive interactions with Asf1 guide H3/H4 transitions among histone chaperones and DNA

Abstract: Anti-silencing function 1 (Asf1) and Chromatin Assembly Factor 1 (CAF-1) chaperone histones H3/H4 during the assembly of nucleosomes on newly replicated DNA. To understand the mechanism of histone H3/H4 transfer among Asf1, CAF-1 and DNA from a thermodynamic perspective, we developed and employed biophysical approaches using full-length proteins in the budding yeast system. We find that the C-terminal tail of Asf1 enhances the interaction of Asf1 with CAF-1. Surprisingly, although H3/H4 also enhances the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 53 publications
10
90
1
Order By: Relevance
“…For example, it will be informative to determine structurally exactly how Vps75 physically interacts with H3. In addition, it will be informative to clarify the relative contribution of Rtt109-Vps75's cytoplasmic and nuclear roles (60) and the in vivo contribution of the Asf1 C terminus to CAF-1 (and other possible) interaction(s) that exist (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it will be informative to determine structurally exactly how Vps75 physically interacts with H3. In addition, it will be informative to clarify the relative contribution of Rtt109-Vps75's cytoplasmic and nuclear roles (60) and the in vivo contribution of the Asf1 C terminus to CAF-1 (and other possible) interaction(s) that exist (36).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast the non-evolutionarily conserved carboxyl terminus of Asf1 is extremely acidic, whereas in humans the region is subject to cell cycle-dependent phosphorylation (33). In S. cerevisiae, functions of the Asf1 C terminus include mediating telomeric silencing (34) and physical interactions with Rad53 (35) and CAF-1 (36).…”
mentioning
confidence: 99%
“…Therefore, Acr-ASF1B adducts or Acr-histone adducts themselves may have no effects on the associations in cells exposed to 100 M Acr. However, reduction of H4K5,12 acetylations due to the formation of Acr adducts might have an impact on the interaction because it has been shown that these modifications are required for the association of histones with ASF1B and importin 4 (31,33,46). To test this possibility, we first established BEAS-2B cells stably expressing FLAG-tagged H3 and determined the levels of H3-interacting proteins before and after Acr exposure by FLAG IP, followed by Western blotting assays.…”
Section: Resultsmentioning
confidence: 99%
“…First, some acetylations, such as H4K5,12ac, are required for the association of histones with translocator protein importin 4 and histone chaperone ASF1 to affect histone nuclear translocation and histone transfer (45,46). Second, the modifications may directly affect chromatin assembly processes by facilitating the deposition of histones to DNA and/or Plasmid supercoiling was not affected by the exposure of either histones or ASF1B to Acr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation